1993
DOI: 10.1002/1098-108x(199311)14:3<319::aid-eat2260140310>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes in dieting disorders

Abstract: This study is an empirical investigation of the prevailing notion that dieting disorder patients have more dysfunctional cognitions and cognitive styles than the nonclinical population. Groups of anorexics, bulimics, normal restrainers, and normal nonrestrainers completed three questionnaires and two repertory grids. Overall, the data supported a cognitive model of dieting disorders. Patients exhibited a lack of awareness of the role played by inner sensations in regulating weight and eating behavior, and emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…Before depression was considered, women with AN scored higher than restrained eaters who scored higher than unrestrained eaters on all measures of shape concern and weight concern, consistent with research by Cooper and Turner (2000). Before depression was considered, women with AN scored significantly lower than restrained eaters on all domains of self-esteem, apart from scholastic and athletic competence, consistent with findings of other researchers (Butow, Beumont, & Touyz, 1993). Restrained eaters only had significantly lower mean scores than unrestrained eaters on physical appearance and global self-esteem.…”
Section: Discussionsupporting
confidence: 85%
“…Before depression was considered, women with AN scored higher than restrained eaters who scored higher than unrestrained eaters on all measures of shape concern and weight concern, consistent with research by Cooper and Turner (2000). Before depression was considered, women with AN scored significantly lower than restrained eaters on all domains of self-esteem, apart from scholastic and athletic competence, consistent with findings of other researchers (Butow, Beumont, & Touyz, 1993). Restrained eaters only had significantly lower mean scores than unrestrained eaters on physical appearance and global self-esteem.…”
Section: Discussionsupporting
confidence: 85%
“…To date, few studies have attempted to examine the exact content of restrained eaters' cognitions as compared to those of unrestrained eaters (Butow, Beumont & Touyz, 1993;French, 1992;Hickford, Ward & Bulik, 1997;Jansen, Merckelbach, Oosterlaan, Tuiten & Van den Hout, 1988) and only two of these have related these cognitions to actual eating behaviour, i.e. food intake in a taste test.…”
Section: Recently Bonifazi and Crowther (1996) Used A Newly Constructementioning
confidence: 99%
“…Supporting these theories, studies have found that anorexics and bulimics tend to view their body as larger than it actually is, be obsessed with their body and bodily functions, and perceive minor bodily flaws as large imperfections (Brouwers, 1988;Fairburn et al, 1998). In addition, studies have found that individuals with eating disorders have more dysfunctional eating-related cognitions than do individuals without these disorders (Butow, Beumont, & Touyz, 1993), and these cognitions contribute to the maintenance of disordered eating patterns .…”
mentioning
confidence: 99%